2016
DOI: 10.1074/jbc.m116.725788
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Acetylation of Histone H3 Decreases Polymerase β Activity on Nucleosome Core Particles in Vitro

Abstract: Histone posttranslational modifications have been associated with changes in chromatin structure necessary for transcription, replication, and DNA repair. Acetylation is one of the most studied and best characterized histone posttranslational modifications, but it is not known if histone acetylation modulates base excision repair of DNA lesions in chromatin. To address this question, we generated nucleosome core particles (NCPs) containingsite-specificallyacetylatedH3K14orH3K56andmea-sured repair of uracil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
4
29
0
Order By: Relevance
“…To accurately determine the effects of translational positioning on the Pol β dRP lyase reaction, we used the 147-bp 601 DNA strong positioning sequence and the recombinant histone octamer from X. laevis ( Supplementary Figure S1A&B ), both of which are known to generate stable well-positioned NCPs. As shown in Supplementary Figure S1C , all substrates were well positioned, independent of the location of the lesion in agreement with previous studies ( 28 , 42 ). Additionally, restriction enzyme accessibility assays of undamaged NCP resulted in the expected occlusion of the HhaI restriction site ( Supplementary Figure S1D ), as shown before ( 28 , 42 ), further confirming the integrity of these designed NCPs.…”
Section: Resultssupporting
confidence: 92%
“…To accurately determine the effects of translational positioning on the Pol β dRP lyase reaction, we used the 147-bp 601 DNA strong positioning sequence and the recombinant histone octamer from X. laevis ( Supplementary Figure S1A&B ), both of which are known to generate stable well-positioned NCPs. As shown in Supplementary Figure S1C , all substrates were well positioned, independent of the location of the lesion in agreement with previous studies ( 28 , 42 ). Additionally, restriction enzyme accessibility assays of undamaged NCP resulted in the expected occlusion of the HhaI restriction site ( Supplementary Figure S1D ), as shown before ( 28 , 42 ), further confirming the integrity of these designed NCPs.…”
Section: Resultssupporting
confidence: 92%
“…Histone acetylation is often associated with increased nucleosomal DNA unwrapping, particularly at distal translational positions (Neumann et al 2009), which could explain the faster repair of 7meG lesions at these positions in highly acetylated nucleosomes. While slower repair near the nucleosome dyad among highly acetylated nucleosomes seems counterintuitive, a recent report suggests that H3K14ac and other histone acetylations (i.e., H3K56ac) inhibit DNA polymerase β activity during repair of lesions located near the dyad of nucleosome substrates in vitro (Rodriguez et al 2016). The opposite trend was observed for histone PTMs associated with the 3 ′ coding regions of yeast genes (e.g., H3K36me3), presumably because these histone PTMs are associated with histone deacetylation (Lee and Shilatifard 2007;Weiner et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear to what extent nucleosomes affect BER in vivo, since nucleosome positioning in eukaryotic genomes is generally weaker than the positioning sequences used for in vitro studies (Mao et al 2017) and the presence of cellular chromatin-remodeling enzymes can facilitate BER in nucleosomes (Hinz and Czaja 2015;Rodriguez et al 2015). Moreover, nucleosomes in vivo are marked by different histone post-translational modifications, which could potentially alter repair efficiency (Rodriguez et al 2016).…”
mentioning
confidence: 99%
“…We recently showed that the effects of histone site-specific acetylation on DNA gap-filling activity by Pol ␤ are dependent on the structural location of the DNA gaps (45). In this study, we wished to determine whether the increased nucleosome dynamics near the DNA ends in ⌬HBR-NCPs was sufficient to allow accessibility to occluded DNA gaps located near the DNA ends (Ϫ49), "midway" (Ϫ21), or near the dyad center (ϩ4).…”
Section: Synthesis By Dna Polymerase ␤ In ⌬Hbr Ncps Depends On the Stmentioning
confidence: 99%